L2 SELVES, EMOTIONS, AND MOTIVATED BEHAVIORS - Teimouri, Yasser (Studies in second language acquisition, 2017)
This study has aimed to investigate language learners’ emotional experiences through the lens of L2 future self-guides. To that end, the L2 motivational self system was chosen as the theoretical framework to relate learners’ emotions to their L2 selves. However, due to inconsistent results of past research concerning the motivational role of the ought-to L2 self, a revision of the model is proposed, discussed theoretically, and tested empirically. The results revealed a trichotomous model of L2 selves—ideal L2 self, ought-to L2 self/own, and ought-to L2 self/others—with distinct motivational profiles. Furthermore, different types of L2 self-discrepancies were found to result in different emotional reactions on the part of L2 learners. Overall, the study provides a clearer picture of L2 learners’ emotions and their motivation in second language acquisition.